Synthesis of N-aryl 2-quinolinones via intramolecular C(sp2)–H amidation of Knoevenagel products. Issue 106 (1st November 2016) - Luo, Laichun; Tao, Kaiqi; Peng, Xiaozhi; Hu, Chunling; Lu, Yuanfeng; Wang, Hong
Abstract : An efficient synthesis of N -aryl 2-quinolinones via K2 S2 O8 -mediated intramolecular C(sp 2 )–H amidation of Knoevenagel products was developed. Abstract : A practical synthesis of N -aryl 2-quinolinones via K2 S2 O8 -mediated intramolecular C(sp 2 )–H amidation of Knoevenagel products was developed. The reaction proceeded smoothly in a biphasic solvent system composed of n -butyl acetate and H2 O.